MANAGEMENT OF THROMBOCYTOPENIA AND FLU-LIKE SYMPTOMS IN DENGUE PATIENTS WITH HERBAL WATER OF EUPHORBIA HIRTA - Mir, Munazza; Khurshid, Rukhshan; Aftab, Roohi (Journal of Ayub Medical College Abbottabad, 2012)
Background: Incidence of dengue increased 30 fold between 1960 and 2010. This increase is believed to be due to a combination of urbanisation, population growth, increased international travel, and global warming. We tried to find out the effect of herbal water of Tawa-tawa, also called Euphorbia hirta, on the flu like symptoms and blood parameters especially on thrombocytopenia. Methods: Total 125 patients with confirmed dengue fever admitted in medical ward of Sir Ganga Ram Hospital Lahore were included in this experimental study. Duration of study was 3 months. Patients were divided into 2 groups, i.e., group A (ages between 30 to 55 years) and group B (ages between 14 to 25 years). A blood sample was obtained on the day of enrolment and after 24 hours of using Tawa-tawa. The variables used were platelet count, haematocrit (HCT), WBC count, serum AST, ALT, IgM/IgG. Results: In men, platelet count was <25,000 and in women, it was >50,000. Haematocrit were >40% in men and 30-40% in women. TLC in a range of 4,000-11,000/mm3 was observed in both males and females. IgM ’˜haemagglutination’ antibody titres (>1:160) was observed in 71.3% females and 50% males. Serum AST was >40 IU/L in 38% females and 36% males. Serum ALT was >40 IU/L in 9.5% females and 12% males. In both group A and B platelet count and TLC were increased nonsignificantly after herbal water of Euphorbia hirta (E. Hirta). Haematocrit value decreased nonsignificantly after using the herbal water. Over 70% of patients showed moderate increase in their platelet count. However leucopoenia improved significantly after the use of aqueous extract of E. hirta. A marked recovery in fever and flu like symptoms was observed. Conclusion: In over 70% patients there was improvement in platelet count, TLC, fever, and flue-like symptoms. Keywords: Dengue, Thrombocytopenia, Euphorbia hirta, Management